(untitled) (Orfeu, 2024)
This article aims to discuss the training and work experiences of musi-cians who have completed higher edu-cation in Music. The proposal was to analyze the challenges faced by highly qualified professionals to enter and re-main in this field, considering a recent context marked by the advancements of neoliberal policies, underfunding of culture, ideological attacks on artistic practice, and restrictions imposed by the Covid-19 pandemic. Without forgetting that artistic work is historically charac-terized by flexibility and informality, we aim to highlight the deepening of uns-table and precarious working conditions, which lead these artist-workers to mo-bilize various everyday survival strate-gies, involving combinations of different activities within and outside the music industry, and even career reorientation. The analyzed data is based on qualitati-ve sociological research focused on the analysis of the trajectories of musicians who are Licenciate in Music by the Fe-deral University of São Carlos (UFSCar) between 2013 and 2023.